MAKNA TELEPON GENGGAM DI KALANGAN MAHASISWA STKIP PGRI SUMATERA BARAT - RIANTO S.Pd, M.Pd, SLAMET (STKIP PGRI Sumatera Barat, 2010)
This research was aimed at identifying hand phone utilization by students at STKIP PGRIWest Sumatera. This research was qualitative. The informant of this research were thestudents who had hand phone who were selected through snowball sampling technique.The data was collected through observation, interview, documentation, and the researcherhimself as an active participant. The data was analyzed by using techniques as suggestedby Miles and Huberman. The finding of this research showed that hand phone utilizationby the students beside it was aimed at its function, as a tool for communication, but it isalso to the owner prestige of him/her will be high. Hand phone symbolized one’s success,modern, and high-tech minded. Hand phone had been a part of students life style today,because they wouldn’t like being a part from old-fashioned class. By having hand phone,students had high self-confidence. Beside that, they will be welcomed to the group ofthose who had hand phone.